The Impact of Mufassir's Beliefs on the Interpretation of the Qur'an: Analysis of the Conception of Istiwa', Kalam, and Ru'yatullah in Tafsir Al-Kasysyaf by Imam Al-Zamakhsyari - Didik Hariyanto,; Abdul Rauf Haris,; M. Aufa, (Technium Education and Humanities, 2024)
The discussion of belief in Islam is an integral part of the Qur'an. Examining the interpretation of verses that talk about Islamic beliefs is a method of gaining a proper understanding of those beliefs. However, the religious background of a person interpreting the text will greatly influence his interpretation of verses that discuss Islamic beliefs. Therefore, it is important to choose a book of tafsir written by mufassir who has a valid belief background. This study examines Imam al-Zamakhshari's interpretation of the nature of istiwa, kalam, and ru'yatullah and the impact of the beliefs held by him on the results of his interpretation. Imam al-Zamakhshari, who had Mu'tazilite beliefs, was the subject of research. Al-Kasysyaf, a work of lugawi exegesis compiled by Imam al-Zamakhshari, was the focus of this study. The purpose of this study is to understand Imam al-Zamakhshari's interpretation of the nature of istiwa', kalam, and ru'yatullah and identify the influence of Mu'tazilite beliefs on the results of the interpretation produced by Imam al-Zamakhshari. This research is a study of characters. The conclusion of this study is as follows: First, Imam al-Zamakhshari interprets the nature of istiwa' as power or istawla, as well as istila'. Regarding the nature of Allah's kalam, Imam al-Zamakhshari explained that Allah speaks by creating these words. Regarding ru'yatullah, Imam al-Zamakhshari interprets the word "ziyadah" in Surah Yunus verse 26 as an additional reward that is a gift from Allah, and interprets the word "nazhirah" in Surah Al-Qiyamah verse 23 as hope and anticipation of favor from Allah. Secondly, the beliefs held by Imam al-Zamakhshari caused him to reject or deny these three qualities in his interpretation.